Peran Moderasi Sensitivitas Etika pada Pengaruh Love of Money dan Machiavellian terhadap Persepsi Etis Mahasiswa Akuntansi - Rizki, Rara Ayu; Aini, Nurul (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2025)
This study aims to examine and analyze the influence of love of money and Machiavellianism on the ethical perceptions of accounting students, as well as to assess the role of ethical sensitivity as a moderating variable. The research sample consisted of 101 accounting students obtained through the distribution of questionnaires to active students of the Accounting Study Program at Wijaya Kusuma University Surabaya in the 2022 and 2023 batches who had taken the Business and Professional Ethics course. The analysis was conducted using a quantitative approach with the Structural Equation Modeling–Partial Least Square (SEM-PLS) method through the SmartPLS 4 application. The results showed that love of money and Machiavellianism had a negative and significant effect on students' ethical perceptions. Ethical sensitivity was found to moderate the influence of love of money on ethical perceptions, but did not moderate the influence of Machiavellianism. These findings indicate that certain personality factors can weaken students' ethical judgments, and that increasing ethical sensitivity through learning can help strengthen the way students assess ethical issues.